Sustainability under research in green energy: A bibliometric study (2018)
The reduction of the amount of pollution and toxicity by the manufacture of products has been a topic widely investigated by many international organizations, looking for an answer that help humanity to minimize the environmental impact. The main objective of this paper is to study the literature of Green engineering from 2007 to 2017 using bibliometric techniques for obtaining an overview of the production behavior of publications in this topic. The information was discharged and analyzed using tools such as Web of Science (WOS) and HistCite to get important results of the international contribution developing significant advances in this area. According to the results obtained, USA has been the most important country researching in this subject, providing 36.8% of the total publications. From the 257 publications, 60.9% were journal articles, where the Abstracts of papers of the American Chemical Society was the most relevant journal with 14 papers. Between 2014 and 2017 an important increase in the published production was presented, being 2016 the year with the most papers published with 15.6% of total investigations. In recent years, green engineering has been consider in many process on industries as a key tool to help the control of the greenhouse emissions, reducing the environmental impact providing some steps to achieve goals proposed for 2050 according to the ISO 50001 standard.Introducción.